2015
DOI: 10.1016/j.biochi.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Sm1 encoding motif in the lsm gene results in distinct changes in the transcriptome and enhanced swarming activity of Haloferax cells

Abstract: Members of the Sm protein family are important for the cellular RNA metabolism in all three domains of life. The family includes archaeal and eukaryotic Lsm proteins, eukaryotic Sm proteins and archaeal and bacterial Hfq proteins. While several studies concerning the bacterial and eukaryotic family members have been published, little is known about the archaeal Lsm proteins. Although structures for several archaeal Lsm proteins have been solved already more than ten years ago, we still do not know much about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 59 publications
2
26
0
4
Order By: Relevance
“…In addition, the Hv SmAP was shown to co-purify with several uncharacterized non-coding RNAs, tRNAs and C/D box snoRNAs ( 28 ). A deletion of the Sm1 motif in the Hv SmAP encoding gene showed a gain of function in swarming, which agreed with the up-regulation of transcripts encoding proteins required for motility ( 32 ).…”
Section: Introductionsupporting
confidence: 57%
“…In addition, the Hv SmAP was shown to co-purify with several uncharacterized non-coding RNAs, tRNAs and C/D box snoRNAs ( 28 ). A deletion of the Sm1 motif in the Hv SmAP encoding gene showed a gain of function in swarming, which agreed with the up-regulation of transcripts encoding proteins required for motility ( 32 ).…”
Section: Introductionsupporting
confidence: 57%
“…In addition, the upstream lsm gene can be terminated within the downstream rpl37e gene. A dicistronic transcript and a rpl37e mRNA were identified by northern blot analysis [30]. A similar independent transcription of genes that are part of the same operon has been described in Sulfolobus islandicus [31].…”
Section: Expression Of Individual Genes In Operonsmentioning
confidence: 52%
“…This phenomenon was confirmed in a previous study experimentally, for instance for the dicistronic operon encoding the proteins Lsm and L37e (HVO_2723 and HVO_2722). Here, a promoter for expression of the rpl37e gene is located in the upstream lsm gene (Supplementary Figure 5) [30]. In addition, the upstream lsm gene can be terminated within the downstream rpl37e gene.…”
Section: Expression Of Individual Genes In Operonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the Haloferax volcanii (Hv) Sm protein binds to several uncharacterized ncRNAs, tRNAs and C/D box snoRNAs ( 18 ), again suggesting a function in tRNA/rRNA processing. A deletion of the Sm1 motif in the Hv SmAP1 encoding gene showed a gain of function in swarming, which was paralleled by an up-regulation of transcripts encoding proteins required for motility ( 24 ).…”
Section: Introductionmentioning
confidence: 99%